Resource management urban agglomerations: principles, methods, tools - Melnikova, Marina (Skhid, 2015)
In article the problem of resource management of urban agglomerations were considered. The role of urban agglomerations in the structure of the national economy of Ukraine was characterized. Features urban agglomerations were identified. These features include the need for cooperation of territorial communities that are part of the urban agglomeration. Cooperation is carried out in the following areas: the development of urban infrastructure, the creation of logistics centers, coordination of urban land use, environmental protection. For projects of cooperation requires resources. Resources urban agglomerations is divided into: natural, human, economic, organizational and legal. Features resources of urban agglomerations were identified. These include: properties, the ability to meet the needs, principles, conditions, ways to attract, determination of the price. Resource management involves the formation, distribution and rational use of resources. The aim, methodology, technology resource management conurbation were identified. Methods of resource management urban agglomerations include: budgeting, programming and project analysis. Were presented resource management tools urban agglomeration: the stages of resource management of socio-economic development; method of estimating the resource potential of the territory. When making decisions on resource management assessed the rationality of their use. The information system includes principles methods, tools, resource management urban agglomerations. This allows you to improve the validity and efficiency of decision-making on management of urban agglomerations.